Corrosion of aluminium - Vargel, Christian (Amsterdam ; Boston : Elsevier, 2004)
This book highlights the practical and general aspects of the corrosion of aluminium alloys with many illustrations and references. In addition to that, the first chapter allows the reader who is not very familiar with aluminium to understand the metallurgical, chemical and physical features of the aluminium alloys. The author Christian Vargel, has adopted a practitioner approach, based on the expertise and experience gained from a 40 year career in aluminium corrosion This approach is most suitable for assessing the corrosion resistance of aluminium- an assessment which is one of the main conditions for the development of many uses of aluminium in transport, construction, power transmission etc. * 600 bibliographic references provide a comprehensive guide to over 100 years of related study * Providing practical applications to the reader across many industries * Accessible to both the beginner and the expert.
Cover -- Half Title Page -- Copyright -- Copyright -- Dedication Page -- Foreword -- Foreword to the Original French Edition -- Introductory Remark -- Preface to the Original French Edition -- Acknowledgements -- Contents -- Part A: Aluminium and Its Alloys -- A.1. The Advantages of Aluminium -- 1.1. LIGHTNESS -- 1.2. THERMAL CONDUCTIVITY -- 1.3. ELECTRICAL CONDUCTIVITY -- 1.4. RESISTANCE TO CORROSION -- 1.5. SUITABILITY FOR SURFACE TREATMENTS -- 1.6. THE DIVERSITY OF ALUMINIUM ALLOYS -- 1.7. THE DIVERSITY OF SEMI-PRODUCTS -- 1.8. THE FUNCTIONALITY OF CASTINGS AND EXTRUSIONS -- 1.9. THE EASE OF USE -- 1.10. RECYCLING -- REFERENCES -- A.2. Physical Properties of Aluminium -- A.3. The Metallurgy of Aluminium -- 3.1. ALLOY SERIES -- 3.2. CASTING ALLOYS -- 3.3. WROUGHT ALLOYS -- REFERENCE -- A.4. The Most Common Wrought Aluminium Alloys -- 4.1. THE 1000 SERIES -- 4.2. THE 3000 SERIES -- 4.3. THE 5000 SERIES -- 4.4. THE 8000 SERIES -- 4.5. THE 2000 SERIES -- 4.6. THE 6000 SERIES -- 4.7. THE 7000 SERIES -- REFERENCES -- A.5. Selection Criteria for Aluminium Alloys -- 5.1. SELECTION CRITERIA -- 5.2. SELECTING AN ALLOY -- 5.3. PRINCIPAL APPLICATIONS OF ALUMINIUM AND ITS ALLOYS -- Part B: The Corrosion of Aluminium -- B.1. The Corrosion of Aluminium -- 1.1. SHORT HISTORICAL INTRODUCTION -- 1.2. THE ELECTROCHEMICAL BASIS OF METAL CORROSION -- 1.3. THE ELECTROCHEMICAL REACTIONS IN THE CORROSION OF ALUMINIUM -- 1.4. THE STANDARD POTENTIAL OF A METAL -- 1.5. DISSOLUTION POTENTIALS -- 1.6. ELECTROCHEMICAL EQUILIBRIUM (POURBAIX) DIAGRAMS -- 1.7. THE ELECTROCHEMICAL BEHAVIOUR OF ALUMINIUM -- 1.8. ALUMINIUM AS A PASSIVE METAL -- REFERENCES -- B.2. Types of Corrosion on Aluminium -- 2.1. UNIFORM CORROSION -- 2.2. PITTING CORROSION -- 2.3. TRANSGRANULAR AND INTERGRANULAR (INTERCRYSTALLINE) CORROSION -- 2.4. EXFOLIATION CORROSION -- 2.5. STRESS CORROSION -- 2.6. FILIFORM CORROSION -- 2.7. WATER LINE CORROSION -- 2.8. CREVICE CORROSION -- 2.9. CAVITATION -- 2.10. EROSION -- 2.11. MICROBIOLOGICAL CORROSION -- 2.12. CORROSION PRODUCTS -- REFERENCES -- B.3. Galvanic Corrosion -- 3.1. ALUMINIUM AND GALVANIC CORROSION -- 3.2. DEFINITION OF GALVANIC CORROSION -- 3.3. FORM OF GALVANIC CORROSION -- 3.4. PRINCIPLE OF A BATTERY -- 3.5. CONDITIONS OF GALVANIC CORROSION -- 3.6. GALVANIC CORROSION PARAMETERS -- 3.7. PRACTICAL ASPECTS OF GALVANIC CORROSION -- 3.8. THE INFLUENCE OF THE TYPE OF METAL IN CONTACT WITH ALUMINIUM IN EMERGED ASSEMBLIES -- 3.9. CONTACT BETWEEN ALUMINIUM ALLOYS -- 3.10. PREDICTING GALVANIC CORROSION -- 3.11. PREVENTION OF GALVANIC CORROSION -- REFERENCES -- B.4. Testing Methods -- 4.1. TYPES OF TESTS -- 4.2. GOAL OF CORROSION TESTING METHODS -- 4.3. EXPRESSION OF RESULTS -- 4.4. STANDARDISATION OF CORROSION TESTING MET.
Includes bibliographical references and index.
Translated from the French.
Keywords: Aluminum -- Corrosion; Electronic books